CP-133 A pharmacoeconomic evaluation in the therapy evolution setting of renal cell carcinoma. (14th February 2016) - Capano, F; Filieri, A; Lerda, C; Buscaino, A; Ielo, D
Abstract : Background: Renal cell carcinoma (RCC) management has changed remarkably in the past years: in 2014, the Italian Medical Oncology Association (AIOM) released its guidelines for RCC management, based on the latest evidence. AIOM recommendations relate to cell histology and risk stratification: Firstline low/intermediate risk: either bevacizumab (combined with interferon-alpha) or sunitinib or pazopanib have proved effective. For high risk: temsirolimus or sunitinib are indicated. Secondline management for both risk categories, tyrosine kinase inhibitor (TKIs) based therapy (sorafenib, axitinib, pazopanib, everolimus). Purpose: Analysing the AIOM guidelines, we wanted to identify, from a pharmacoeconomic point of view, the best RCC clinical treatment approach. Material and methods: Using the RCC treatment algorithm, we evaluated drug clinical efficacy data that were used to calculate the effectiveness of each treatment (evaluating effectiveness, response rate and discontinuation rate). Cost/effectiveness (C/E) pharmacoeconomic analysis was performed from a National Health System (NHS) point of view, where the efficacy data were inferred from the submitted studies and the costs were calculated assuming a therapy duration equal to progression free survival (PFS), net of AIFA discounts, considering local prices. For both risk categories, the analysis was performed on the possible treatments within which the efficacy and cost data were the result of first and secondline treatments. Results: Within the low/intermediate risk category, sunitinib-I line+sorafenib-II line (C/E=3172€/month) had the most favourable C/E ratio; the least favourable was pazopanib-I line+everolimus-II line (C/E=3734€/month). In the high risk category, sunitinib-I line+sorafenib II line (C/E=2776€/month) had the best C/E profile, and the least favourable was temsirolimus-I line+everolimus-II line (C/E=4000€/month). Considering only effectiveness, the best treatment was in the low/intermediate risk group, obtained with bevacizumab+IFN (I line)+axitinib (II line), with a C/E corresponding to 3544€/month and 22.3 months PFS. In high risk group, the best treatment was with sunitinib-I line+axitinib II line with a C/E corresponding to 3248€/month and a PFS of 10.6 months. Conclusion: Considering the C/E profile, the results were homogeneous, both in low risk (PFS=14.6–22.3; C/E=3172 to 3734) and in high risk (PFS=8.5–12; C/E=2776–4000). This study will be the starting point to find the best RCC therapeutic strategy. No conflict of interest.